2013
DOI: 10.1128/jvi.02762-12
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Variability and the Classification of Hepatitis E Virus

Abstract: bThe classification of hepatitis E virus (HEV) variants is currently in transition without agreed definitions for genotypes and subtypes or for deeper taxonomic groupings into species and genera that could incorporate more recently characterized viruses assigned to the Hepeviridae family that infect birds, bats, rodents, and fish. These conflicts arise because of differences in the viruses and genomic regions compared and in the methodology used. We have reexamined published sequences and found that synonymous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
113
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 41 publications
3
113
0
Order By: Relevance
“…Four major genotypes have been defined, and two additional genotypes infecting wild boars have been suggested (2,3). Genotypes 1 and 2, which mainly infect humans, have been described in Asia, Africa, or Mexico, whereas genotypes 3 and 4 have been described worldwide.…”
mentioning
confidence: 99%
“…Four major genotypes have been defined, and two additional genotypes infecting wild boars have been suggested (2,3). Genotypes 1 and 2, which mainly infect humans, have been described in Asia, Africa, or Mexico, whereas genotypes 3 and 4 have been described worldwide.…”
mentioning
confidence: 99%
“…On field samples, the singleplex real-time RT-PCR assays detected at least 34-fold more positive samples than the duplex real-time RT-PCR assays. The design of a broadly reactive assay for detection of mHEV genotypes is a complex and challenging task due to the heterogeneity among the various HEV strains (5,29). The sensitivities of real-time assays can vary widely depending on the target region and HEV genotype (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Degeneracies may reduce the sensitivity and specificity of an assay due to factors such as a lower effective concentration of each primer or difficulties in estimating the suitable annealing temperatures and primer lengths (31), which could partially explain the poor results achieved with assays B, C, and D compared with assay A in the present study. Analysis of the full-length genomes of various human and animal mHEV strains revealed that the HEV genomes vary even in the conserved regions (5,29), and this genetic variability complicates reliable detection of different mHEV genotypes and subtypes. In fact, recent studies found polymorphisms in the region of the probe-binding site of the most widely used real-time RT-PCR assay for HEV detection (assay A) (17), and a modification of the probe and subsequent increase of the melting temperature restored detection of the polymorphic strains (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Genotypes 3 and 4 are generally less pathogenic, and are enzootic in a variety of wild and domestic animals, in particular wild boar and pigs [4,7,8]. Lately, HEV has been detected in bats and rodents [9,10,11], indicating that these mammals may be a reservoir for HEV and an additional source for transmission to humans. The classification of HEV variants is currently in transition without agreed definitions for genotypes and subtypes or for deeper taxonomic groupings into species and genera.…”
Section: Introductionmentioning
confidence: 99%
“…The classification of HEV variants is currently in transition without agreed definitions for genotypes and subtypes or for deeper taxonomic groupings into species and genera. Smith and coworkers [9] recommend a genetic classification of HEV into 4 species as follows: group A, HEV isolates that infect humans or are closely related to such isolates (genotypes 1-4, the 2 wild boar isolates, and the rabbit isolates); group B, avian HEV; group C, bat HEV; and group D, rat HEV and ferret HEV. The more divergent HEV-like virus from fish (cut-throat trout virus) would represent a plausible candidate member of a second genus within the Hepeviridae .…”
Section: Introductionmentioning
confidence: 99%